Rozwój kariery jako proces inwestowania w kapitał kariery - Cybal-Michalska, Agnieszka (Wydawnictwo Naukowe UAM, 2012)
This article presents a discourse about the subject of careers; a discourse, which demands tak-ing into account multicontextual changes in the job world, that make employees face new re-quirements. The increase of roles ascribed to careers and the ability to plan, manage and moni-tor one’s career in the lifelong perspective are the most important requirements. The article noticeably stresses the subjective tinge of the career phenomenon. Career capital comprises of values that create career competence and that are useful in its constitution and development. It means that the career capital (which can increase, but which can also lose its value or be ex-changed for a “fresh” one) is a term reflecting in an individual’s mind a diagnosis and a progno-sis of accumulative individual resources, acquired in the course of educational, professional, social and cultural experience. There is no doubt that while analysing individual paths of a career development, one should include a wide spectrum of an individual’s determinants, as well as, one should examine semantic meanings that a subject ascribes to the reality in order to interpret and understand one’s past and new feelings and experiences.
The development of a career as a process of investing in a career capital
Keywords: career capital; investing and refreshing career capital; career development; matur-ity in careers; career portfolio; career competence model